Integrazioni di tecnologie e processi per il Monitoraggio Strutturale su ampia scala - Marsella, Maria; D'aranno, Peppe; Moriero, Ilario; Acunzo, Gianluca; Vicentino, Michele; Bottaro, Antonio (GEOmedia, 2019)
The integration of DInSAR satellite data and in-situ sensors significantly improve long-term structural monitoring, contributing to reduce potential risk of damages or failures. Collecting and sharing monitoring data through an IoT infrastructure ensures a constant and secure access to the information by professional users' networks that are often urged to take decisions and activate further investigations. By implementing such integrated systems, a more effective and widespread monitoring of existing building stocks can be achieved